Usaha Budidaya Itik Pedaging Jenis Hibrida dan Peking - M Ridwan; R Sari; R D Andika; A A Candra; G G Maradon (Politeknik Negeri Lampung, 2019)
Broiler ducks are ducks that are able to grow fast and can efficiently convert feed into meat with high nutritional value. Broiler ducks have good flesh structure and structure. The good meat structure of broilers is now becoming more popular among the people, because the taste of the meat is tasty and tasty. Broiler ducks known by the public include hybrid ducks and Peking ducks. The ever-increasing need for duck meat is not matched by the availability of enough duck meat in the market, to meet the needs of the community. This could be the potential to cultivate broilers as evidence that poultry business and agribusiness, especially ducks are still wide open with promising profit prospects. The method used is: to maintain broilers totaling 50, each of which consists of 25 hybrid ducks and peking 25 tails, then feeding and drinking, taking data through recording weighing weight, and analyzing the profitability of broiler duck farming. Based on maintenance for 42 days, the data obtained was the consumption of 3.645 g / tail hybrid rations and the consumption of 3.727g pork duck / tail, United Nations hybrid duck 1.168,8 g and peking duck 1.171,04 g, FCR hybrid duck 3.11 and Peking duck 3.18 and hybrid duck mortality 4% and Peking 12%. Weight gain, mortality, and conversion of Peking duck feed were higher than hybrid ducks.Â Keywords: hybrid duck, Peking duck, Production PerformÂ